The concept of internet rights policy in Indonesia: A comparison from United States, European Union and Malaysia - Hutagalung, Gunawan; Hartiwiningsih; Gusti Ayu Ketut Rachmi Handayani, I (Edelweiss Applied Science and Technology, 2024)
The regulatory framework related to internet access is one of the criteria that influences a country’s level of digital competitiveness. Valuable lessons need to be learned from countries that have a better level of digital competitiveness than Indonesia. This article proposes a concept for regulating internet access rights in Indonesia in the era of digital transformation to increase Indonesia's digital competitiveness. Research methods used are analytic normatiques with a normative- based approach that USES secondary data sources of legislation, legal theories, principles of law and opinions by scholars. Research shows that there is a correlation between the framework's regulatory levels as a sub-grading factor with a country's final digital competitiveness rating so that a legal certainty can determine a country's digital competitiveness level. Indonesia has, to date, almost no certainty of the law. In contrast with countries in the United States, the European Union, and Malaysia, which already have clear, unequivocal legislation and regulation that govern Internet privileges.